Impact of covid-19 on event industry: Event audience readiness towards event digitization - Marry Tracy Pawan; Juliana Langgat (Penerbit UMT, 2021)
For the event organiser, Sabah is one of the states that becomes a focal point. As Sabah is one of the most popular tourist destinations, several large events such as the Sabah Jazz Festival, Pesta Lepa-lepa, Pesta Kaamatan, Pesta Kalimaran, and other festivals have been held. However, COVID 19’s disruptive impacts have had such a significant impact on the event sector. Most of the events are getting cancelled or postponed all over the world. Over the past several months, a significant number of meetings and conferences have been redesigned as virtual events. However, the event industry needs to know the readiness of the public towards the shifting from the physical to the digital. Therefore, the objective of this research is to determine the event audience readiness for digital events. It is important for the event industry to know the readiness and a good online platform in providing a good service to their audience. A quantitative method was used to conduct this study. The main finding will see how far our communities is ready to adapt the new norm. Based on the finding it shows that event audience are willing to adopt the event digitisation, and this is due to the impact of the COVID 19pandemic which was accelerating changes in event audience behaviour. This research will benefit the event organisers and help them prepare strategic plana to cater to the audience needs.